A Long-Term Evaluation of Facebook for Recruitment and Retention in the ENDIA Type 1 Diabetes Pregnancy-Birth Cohort Study. (May 2023) - McGorm, Kelly J.; Brown, James D.; Thomson, Rebecca L.; Oakey, Helena; Moore, Belinda; Hendry, Alexandra; Colman, Peter G.; Craig, Maria E.; Davis, Elizabeth A.; Harris, Mark; Harrison, Leonard C.; Haynes, Aveni; et al.
Background: The Environmental Determinants of Islet Autoimmunity (ENDIA) study is an Australia-wide pregnancy-birth cohort study following children who have a first-degree relative with type 1 diabetes (ACTRN1261300794707). A dedicated ENDIA Facebook page was established in 2013 with the aim of enhancing recruitment and supporting participant retention through dissemination of study information. To measure the impact of Facebook, we evaluated the sources of referral to the study, cohort demographics, and withdrawal rates. We also investigated whether engagement with Facebook content was associated with specific post themes. Methods: Characteristics of Facebook versus conventional recruits were compared using linear, logistic, and multinomial logistic regression models. Logistic regression was used to determine the risk of study withdrawal. Data pertaining to 794 Facebook posts over 7.5 years were included in the analysis. Results: Facebook was the third largest source of referral (300/1511; 19.9%). Facebook recruits were more frequently Australian-born ( P < .001) enrolling postnatally ( P = .01) and withdrew from the study at a significantly lower rate compared with conventional recruits (4.7% vs 12.3%; P < .001) after a median of follow-up of 3.3 years. Facebook content featuring stories and images of participants received the highest engagement even though <20% of the 2337 Facebook followers were enrolled in the study. Conclusions: Facebook was a valuable recruitment tool for ENDIA. Compared with conventional recruits, Facebook recruits were three times less likely to withdraw during long-term follow-up and had different sociodemographic characteristics. Facebook content featuring participants was the most engaging. These findings inform social media strategies for future cohort and type 1 diabetes studies. Trial Registration: Australia New Zealand Clinical Trials Registry: ACTRN1261300794707.